Clinical Assessment of Bortezomib for Multiple Myeloma in Comparison with Thalidomide - Mitsutoshi Satoh; Rieko Oguro; Chigusa Yamanaka; Katsutoshi Takada; Yasuhiro Matsuura; Toyomi Akiba; Nobuyuki Aotsuka; Yoshihiro Tani; Hisashi Wakita (Frontiers Media S.A., 2011)
Purpose: We studied the efficacy and safety of bortezomib (BOR) for treatment of multiple myeloma in comparison with thalidomide (THAL) by reference to adverse events, and searched for laboratory markers that could be used for prognostication of patients. Methods: Biochemical data of patients receiving BOR and THAL for treatment of multiple myeloma at the Japanese Red Cross Narita Hospital were investigated retrospectively, after obtaining Institutional Review Board approval. Judgment of curative effects complied with the effects criteria of the International Myeloma Working Group (IMWG) [1]. Results: BOR showed a higher rate of effectiveness than THAL for refractory multiple myeloma, and its effects were rapid. BOR treatment prolonged the survival time of THAL-resistant patients. The efficacy of BOR was unrelated to patient age, the number of previous therapeutic regimens, or the disease period. After medication with BOR, patients in whom it had been effective tended to show an increase of the serum alkaline phosphatase (ALP) level. Thrombocytopenia (86.2%) and leucopenia (69.0%) were observed at high frequencies, but no previously unreported adverse events or fatalities were associated with BOR therapy. Conclusion: It is suggested that BOR has therapeutic efficacy for multiple myeloma as a first-line medical treatment and/or for patients with THAL resistance, and can improve prognosis and survival. Since serum ALP elevation was observed in many patients for whom BOR was effective, this may be a predictor of BOR efficacy.